High-frequency ultrasound combined with shear wave elastography to evaluate the efficacy of lymphaticovenular anastomosis in patients with secondary lymphedema - Yu, Haige; Zhang, Shuo; Zhu, Haohui; Ding, Xiao; Wu, Chengkai; Xu, Chenjing; Song, Yan (Frontiers in Surgery, 2025)
PurposeHigh-frequency ultrasound combined with shear wave elastography (SWE) was used to evaluate the efficacy of lymphaticovenular anastomosis (LVA) in treating secondary lymphedema.Materials and methodsThis study included 40 patients with secondary lymphedema who underwent LVA at the Department of Vascular Surgery, Henan Provincial People's Hospital, from October 2023 to October 2024. Limb circumference measurements, bioelectrical impedance analysis (BIA), and high-frequency ultrasound combined with SWE were conducted before and after treatment. Changes in subcutaneous echo-free space (SEFS) grading and elastic parameters were analyzed pre- and post-treatment.ResultsFollowing LVA, the percentage of excess volume (PEV) and the extracellular water/total body water (ECW/TBW) ratio in the affected limb significantly decreased (P < 0.001). SEFS scores of the subcutaneous tissue also showed statistically significant changes (P < 0.001). Additionally, the shear wave velocity (SWV) of the dermis decreased, while that of the subcutaneous tissue layer increased, both with statistical significance (P < 0.001). The difference in SEFS scores between pre- and post-treatment was statistically significant (P < 0.001), supporting the finding that SWV decreased in the dermis and increased in the subcutaneous tissue layer (P < 0.001).ConclusionThe reduction in SEFS in the affected limb after LVA, along with the decreased SWV in the dermis and increased SWV in the subcutaneous tissue layer, suggests that LVA effectively reduces lymphatic fluid retention across all tissue layers. This provides novel ultrasonographic evidence for assessing and refining treatment efficacy and follow-up.